Demonstrated preference in the Austrian economic analysis - Megger, Dawid (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2024)
This paper is an attempt to clarify the concept of demonstrated preference in the economic analysis of the Austrian School of Economics. It considers several interpretations of this concept: (1) as a thymological concept which matters in empirical interpretations of concrete human actions; (2) as a preference expressed in voluntary actions; (3) as the only existing preference; (4) as the only preference which matters in economics; (5) as the only preference which matters in the economy. It is argued that despite the Austrian insistence on (4), the only interpretation resistant to criticism is (5). Unfortunately, it is not sufficient to draw or reinforce the conclusions that Murray N. Rothbard and his followers reach in their considerations on welfare economics, monopoly theory, public goods theory, and game theory. A number of additional clarifications are also made (e.g., the concepts of “voluntariness” and “psychologizing” in economics).
Keywords: demonstrated preference; revealed preference; Murray N. Rothbard; Austrian School of Economics